1989
DOI: 10.1111/j.1540-8191.1989.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Concept for a Bileaflet Atrioventricular Valve that Maintains Annular-Papillary Muscle Continuity

Abstract: We have developed a simplified concept for a bileaflet atrioventricular prosthesis that can be constructed from a simple sheet of glutaraldehyde preserved pericardium. The valve has no rigid ring or stent and no cloth sewing ring. Insertion of the valve reestablishes normal continuity between the annulus and the papillary muscles. We have replaced the mitral valve in nine dogs using this prosthesis. All valves have been competent with excellent valve opening areas as confirmed by echo-Doppler assessment. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To prevent the loss of mitral continuity and rigidity of the annulus, stentless and chorda mounted valves have been developed (7–9) and mitral homografts or stentless allografts have been used in mitral valve replacement (4,5). However, these types of valves are not commonly employed for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent the loss of mitral continuity and rigidity of the annulus, stentless and chorda mounted valves have been developed (7–9) and mitral homografts or stentless allografts have been used in mitral valve replacement (4,5). However, these types of valves are not commonly employed for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Newly designed bioprosthetic mitral valves with chordae have been evaluated by implanting a new valve in the mitral position in experimental animals (7–9). We believe that this mitral adapter could also be useful to evaluate prosthetic mitral valves with chordae and that endoscopic examination may enable precise and detailed examination of the valves.…”
Section: Discussionmentioning
confidence: 99%
“…Tubular sleeves have been made of untreated and aldehydetanned autogenous pericardium, as well as aldehyde-tanned xenograft pericardium. [4][5][6] In most, the anterior part of the tube is deeper than the posterior so the closure line has a curve that is somewhat parallel to the mural annulus. Ventricular attachment has generally been to the inside of each papillary muscle at the commissures between the deeper anterior leaflet and the shallower posterior leaflet.…”
Section: Tubular Sleeves Of Biological Tissuementioning
confidence: 99%
“…In my experience of copying and testing valves of this type in vitro and in vivo, and in my observations of the designs of others implanted in animals and humans, I have observed that the pericardium representing the posterior leaflet commonly develops folds in closure. 5 These folds give the appearance of multiple scallops. With a contractile annulus and a supple sewing "ring," nature reproduces in closure the natural scalloped form of the native mitral valve.…”
Section: Tubular Sleeves Of Biological Tissuementioning
confidence: 99%